If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + -13p + 12q + -5 + 2p + -15q = 0 Reorder the terms: 21 + -5 + -13p + 2p + 12q + -15q = 0 Combine like terms: 21 + -5 = 16 16 + -13p + 2p + 12q + -15q = 0 Combine like terms: -13p + 2p = -11p 16 + -11p + 12q + -15q = 0 Combine like terms: 12q + -15q = -3q 16 + -11p + -3q = 0 Solving 16 + -11p + -3q = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -11p + -16 + -3q = 0 + -16 Reorder the terms: 16 + -16 + -11p + -3q = 0 + -16 Combine like terms: 16 + -16 = 0 0 + -11p + -3q = 0 + -16 -11p + -3q = 0 + -16 Combine like terms: 0 + -16 = -16 -11p + -3q = -16 Add '3q' to each side of the equation. -11p + -3q + 3q = -16 + 3q Combine like terms: -3q + 3q = 0 -11p + 0 = -16 + 3q -11p = -16 + 3q Divide each side by '-11'. p = 1.454545455 + -0.2727272727q Simplifying p = 1.454545455 + -0.2727272727q
| 3(s+24.5)=150 | | 4-x^2-3x=0 | | 19/17=q/16 | | a^2x+(a-8)=(a+8)x | | 2.8+0.56= | | 3(x-3)+7=10 | | 7v^2+12=0 | | -7+d-6+2d= | | -2.8+0.56= | | x(t)=u(t+1)-2u(t-1)+u(t-3) | | 2+9=16 | | 9p^2=8p-1 | | 15x-15y+90= | | 5xsquared-7x-29=0 | | X^2+y^2-2x-2y=2 | | 5+4=4d | | 7x-7=x+4 | | 4x^4-6x^4= | | 4y=-1x | | 4x+47=6-13x | | 4m-5m+10=1 | | X-22.9=44.4 | | 2c+12=8c | | 7x+15=1.5+12x | | x^3+9x^2-9x-81=0 | | 11y-75=4y | | X^2+y^2+2x+-6y+7=0 | | y+40=11y | | x*(x^2+6*x+25)= | | 19y-2=17y | | 3(3a-1)= | | 2y=4y-14 |